2023
DOI: 10.3390/ma16216833
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Combined Influence of Temperature and Humidity on Fatigue Crack Growth Rate in Al6082 Alloy in a Coastal Environment

Ibrahim Alqahtani,
Andrew Starr,
Muhammad Khan

Abstract: The fatigue crack growth rate (FCGR) of aluminium alloys under the combined influence of temperature and humidity remains a relatively unexplored area, receiving limited attention due to its intricate nature and challenges in predicting the combined impact of these factors. The challenge was to investigate and address the specific mechanisms and interactions between temperature and humidity, as in coastal environment conditions, on the FCGR of aluminium alloy. The present study conducts a comprehensive investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…It was also shown that a test frequency increase from 25 to 100 Hz did not have any effect on the material fatigue life. More recent studies [119,120] also showed the detrimental effect of the environment on the fatigue life of 6082 aluminum alloy.…”
Section: Corrosion Fatigue Of Al-mg-si-(cu) Alloysmentioning
confidence: 97%
“…It was also shown that a test frequency increase from 25 to 100 Hz did not have any effect on the material fatigue life. More recent studies [119,120] also showed the detrimental effect of the environment on the fatigue life of 6082 aluminum alloy.…”
Section: Corrosion Fatigue Of Al-mg-si-(cu) Alloysmentioning
confidence: 97%
“…Bergner et al [187] used the curve fitting technique to correlate Paris constants C and m and obtained the linear fit with R 2 = 0.96. Alqahtani et al [188] utilised the curve fitting method to find the Paris constants C and m from the Paris equation for different temperature and humidity conditions. The regression equations obtained by curve fitting were linear for fatigue life cycles and C.…”
Section: Modelling and Predictive Approachesmentioning
confidence: 99%
“…The study also compared the fatigue behavior of AA2198-T8 and AA2024-T3 alloys, emphasizing the differences in fracture surface morphology, crack propagation rate, and the presence of micro and interlayer cracks. Alqahtani [11] conducted a comprehensive study on the effects of temperature and humidity on Al6082 alloy FCGR. An empirical model was also established to accurately predict the fatigue life cycle values under these environmental conditions.…”
Section: Introductionmentioning
confidence: 99%